Spectral and temporal features of seismic events during the movement of heavy equipment and the action of certain types of weapons - Britsky, A. I. (Інститут проблем реєстрації інформації НАН України, 2020)
Experimental seismograms obtained as a result of the movement of heavy equipment and the action of certain types of weapons are presented and analyzed. The measurements were carried out in the field and at a military training ground. In this case, seismometers with digital laser interferometers were used. The features of such seismometers are high accuracy and resolution at the level of a few nanometers. Such seismometers measure the displacement of the earth's surface, rather than speed or acceleration. If necessary, estimates of speed or acceleration can be obtained through calculations. Suburban, passenger and freight trains were considered as accessible heavy equipment. The study of the actions of certain types of weapons was carried out during real firing at a military training ground. At the same time, seismograms of the strikes of the base plate of a mortar caliber of 120 mm and the shots of the D-30 howitzer were recorded. A qualitative analysis of the results of the study showed good agreement with the results obtained by US scientists at the Baghdad Seismic Observatory. Seismic portraits of the investigated events in the time and frequency domains are obtained. In the future, they will be used to solve problems of identification and location of such events. Fig.: 10. Refs: 6 titles.